Prognostication of production of goods on the basis of fuzzy sets - Totska, Olesia Leontiivna; Тоцька, Олеся Леонтіївна; Nedelea, Alexandru; Неделя, Александру (The Annals of the Stefan cel Mare University of Suceava, Fascicle of the Faculty of Economics and Public Administration, 2009)
In the article an authors forecast the issue of commodities by the enterprises of food retail industry of the Volyn region of Ukraine by the use of the fuzzy sets theory. The algorithm of such foresight consists in passing of the following stages: construction of dynamic rows of issue of ten basic food stuffs in the last few years; equipping them after growth; construction fuzzy interval for every commodity; determination optimistic estimation for every index. On the basis of obtained information the general issue of food products is calculated also in next years. Determination of optimistic estimation is conducted after the original method developed by an author. Basic its idea consists in that an interval which answers the “golden” mean of dynamic row is most credible. У статті автори прогнозують випуск товарів підприємствами харчової промисловості Волинської області України за допомогою використання теорії нечітких множин. Алгоритм такого передбачення полягає у проходженні наступних етапів: побудова динамічних рядів випуску десяти основних продуктів харчування за останні роки; впорядкування їх за зростанням; побудова для кожного товару нечіткого інтервалу; визначення оптимістичної оцінки для кожного показника. На підставі отриманої інформації обчислюється також загальний випуск продовольчої продукції у наступні роки. Визначення оптимістичної оцінки проводиться за оригінальною методикою, розробленою автором. Основна її ідея полягає в тому, що найбільш імовірним є інтервал, який відповідає “золотій” середині динамічного ряду.
Прогнозування виробництва продукції на основі нечітких множин
Keywords: fuzzy intervals; нечіткі інтервали; food retail industry; харчова промисловість; production of goods; виробництво продукції; optimistic estimation; оптимістична оцінка; pessimistic estimation; песимістична оцінка